Impact of Conditioning Intensity and Genomics on Relapse After Allogeneic Transplantation for Patients With Myelodysplastic Syndrome. (December 2021) - Dillon, Laura W.; Gui, Gege; Logan, Brent R.; Fei, Mingwei; Ghannam, Jack; Li, Yuesheng; Licon, Abel; Alyea, Edwin P.; Bashey, Asad; Devine, Steven M.; Fernandez, Hugo F.; Giralt, Sergio; et al.
Abstract : PURPOSE : Patients with myelodysplastic syndrome (MDS) are at risk of relapse after allogeneic hematopoietic cell transplantation. The utility of ultra‐deep genomic testing to predict and the impact of conditioning intensity to prevent MDS relapse are unknown. METHODS : Targeted error‐corrected DNA sequencing was performed on preconditioning blood samples from patients with MDS (n = 48) from the Blood and Marrow Transplant Clinical Trials Network 0901 phase III randomized clinical trial, which compared outcomes by allogeneic hematopoietic cell transplantation conditioning intensity in adult patients with < 5% marrow myeloblasts and no leukemic myeloblasts in blood on morphological analysis at the time of pretransplant assessment. Clinical end points (53‐month median follow‐up) included transplant‐related mortality (TRM), relapse, relapse‐free survival (RFS), and overall survival (OS). Of the 48 patients examined, 14 experienced TRM, 23 are relapse‐free, and 11 relapsed, of which 7 died. RESULTS : Using a previously described set of 10 gene regions, 42% of patients (n = 20) had mutations detectable before random assignment to reduced intensity conditioning (RIC) or myeloablative conditioning (MAC). Testing positive was associated with increased rates of relapse (3‐year relapse, 40% v 11%; P = .022) and decreased OS (3‐year OS, 55% v 79%, P = .045). In those testing positive, relapse rates were higher (3‐year relapse, 75% v 17%; P = .003) and RFS was lower (3‐year RFS, 13% v 49%; P = .003) in RIC versus MAC arms. Testing additional genes, including those associated with MDS, did not improve prognostication. CONCLUSION : This study provides evidence that targeted DNA sequencing in patients with MDS before transplant can identify those with highest post‐transplant relapse rates. In those testing positive, random assignment to MAC lowered but did not eliminate relapse risk.